2008
DOI: 10.1038/sc.2008.5
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity, pain interference and characteristics of spinal cord injury

Abstract: Study Design: Postal survey. Objectives: To examine if the intensity of pain in persons with spinal cord injury (SCI) varied as a function of pain site, and to identify the patient and SCI characteristics associated with pain location, pain intensity and pain interference in a sample of persons with SCI. Setting: Community sample, United States. Methods: A postal survey including measures of pain intensity, pain interference, other pain, demographic and medical characteristics was completed by 238 adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
66
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 17 publications
12
66
2
2
Order By: Relevance
“…4,22,23 In addition, SCI characteristics such as age at SCI, duration after SCI and completeness of injury were not related to pain ratings. 8 It has been shown that incomplete spinal injuries were more likely to result in pain than complete injuries, whereas no significant association between the severity of pain and completeness of injury was found. 4 Similarly, other than the completeness of injury and employment status, we could not find any significant demographic variable to be in association with pain intensity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4,22,23 In addition, SCI characteristics such as age at SCI, duration after SCI and completeness of injury were not related to pain ratings. 8 It has been shown that incomplete spinal injuries were more likely to result in pain than complete injuries, whereas no significant association between the severity of pain and completeness of injury was found. 4 Similarly, other than the completeness of injury and employment status, we could not find any significant demographic variable to be in association with pain intensity.…”
Section: Discussionmentioning
confidence: 92%
“…For many of them, the pain is severe and accompanied by reduced physical functioning, eventually lowering the QoL. 8 Further, chronic pain and psychological disorders are closely related, affecting physical and psychosocial functioning. Likewise, studies show that an important proportion of SCI patients are depressed when compared with healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…This situati on does not contribute to the rehabilitati on of SCI pati ents, as sports, physical exercise and leisure are fundamental for this goal. Sports permits the development of physical and psychological aspects, enhances independence and broadens treatment and socializati on alternati ves (20) . This phenomenon was identi fi ed in a study (21) developed in Canada, in a sample of 90 SCI pati ents, which associated sports practi ce, community integrati on and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Parti ciparon 47 sujetos con media etaria de 42,95 años, 91,5% de sexo masculino y 8,5% femenino. Los dominios obtuvieron estos puntajes: fí sico (58,59), psicológico (63,82), social (68,82) y ambiental (55,20). Mediante regresión lineal múlti ple, se verifi có la correlación de los puntajes de los dominios con la percepción de la QV: fí sico (p<0,187), psicológico (p<0,399), social (p<0,000) y ambiental (p<0,008).…”
unclassified
“…Vall et al 16 , in a descriptive cross-sectional study conducted on 109 patients with SCI, reported that most individuals affected were male, younger than 40 years, with incomplete lesions; these results were also not statistically different. Ullrich et al 17 did not find any correlation between pain prevalence and demographic and medical variables.…”
Section: Resultsmentioning
confidence: 99%